Analisis Resepsi pada Gangguan Mental Bipolar dalam Film Ku Kira Kau Rumah - Ilmiawan Noor Rachim; Arif Ardy Wibowo (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
A mental health issue that has been of concern to the public in recent years is bipolar mental disorder. The disorder has an impact on increasing mortality rates, especially death by suicide. One of the Indonesian movies that raised the theme of bipolar mental disorder is the movie Ku Kira Kau Rumah. This research aims to find out how the audience perceives the content of the message, especially regarding Bipolar mental disorder in the movie Ku Kira Kau Rumah. This research uses a descriptive qualitative approach with the method of reception analysis by Stuart Hall based on three categories namely Dominant Hegemonic Position, Negotiate Position and Oppositional Position using primary data sources as the main source. The data collection techniques used were interviews with eight informants and documentation. The data analysis technique used is the Miles and Huberman model including data reduction, data display and conclusion drawing and the data validation technique is source triangulation. Based on the results of the research data analysis, it was concluded that two informants were in the dominant hegemonic position, meaning that the two informants approved the message conveyed. Then three informants are in a positive negotiated position, meaning that the informant tends to agree with the message conveyed in the film and the last three informants are in an oppositional position, which means that the informant who is in the positive position does not agree with the message conveyed in the film.